Solid and Semisolid Innovative Formulations Containing Miconazole-Loaded Solid Lipid Microparticles to Promote Drug Entrapment into the Buccal Mucosa - Viviana De Caro; Libero Italo Giannola; Giulia Di Prima (Pharmaceutics, 2021)
The currently available antifungal therapy for oral candidiasis (OC) has various limitations restricting its clinical use, such as short retention time, suboptimal drug concentration and low patients compliance. These issues could be overcome using micro or nanotechnology. In particular, solid lipid microparticles (SLMs) resulted as a particularly promising penetration enhancer carrier for lipophilic drugs, such as the antifungal miconazole (MCZ). Based on these considerations, cetyl decanoate (here synthesized without the use of metal catalysis) was employed together with 1-hexadecanol to prepare MCZ-loaded SLMs. These resulted in a powder composed of 45–300 µm diameter solid spherical particles, able to load a high amount of MCZ in the amorphous form and characterized by a melting temperature range perfectly compatible with oromucosal administration (35–37 °C). Moreover, when compared to Daktarin® 2% oral gel in ex vivo experiments, SLMs were able to increase up to three-fold MCZ accumulation into the porcine buccal mucosa. The prepared SLMs were then loaded into a buccal gel or a microcomposite mucoadhesive buccal film and evaluated in terms of MCZ permeation and/or accumulation into porcine buccal mucosa by using lower doses than the conventional dosage form. The promising results obtained highlighted an enhancement in terms of MCZ accumulation even at low doses. Furthermore, the prepared buccal film was eligible as stable, reproducible and also highly mucoadhesive. Therefore, the formulated SLMs represent a penetration enhancer vehicle suitable to reduce the dose of lipophilic drugs to be administered to achieve the desired therapeutic effects, as well as being able to be effectively embedded into easily administrable solid or semisolid dosage forms.